Using Google+ for carrying laboratory practices in cooperation between universities - Joan Puig-Ortiz; Rosa Pàmies-Vilà; Jordi Ramon Martínez Miralles (OmniaScience, 2015)
This communication presents a proposal for cooperation among universities to improve curricula that require laboratory practices. It proposes a methodology to implement an innovative educational project of exchanging laboratory practices. The exchange of laboratory practices can be developed at different levels of interaction that require different levels of complexity in the assembly of practices. A first experience took place in the area of machine design. The social network chosen was Google+. Teaching material was shared through a community of Google+ (notes, videos, scripts practices ...). And the practice was developed through Google Hangout. The final survey made shows students' satisfaction about the development of the experience.